Biomarkers of exposure, antibodies, and respiratory symptoms in workers heating polyurethane glue. Issue 3 (March 1996) - Skarping, G; Dalene, M; Svensson, B G; Littorin, M; Akesson, B; Welinder, H; Skerfving, S
Abstract : OBJECTIVES: The pathogenic basis of respiratory disorders associated with isocyanates are still obscure. One reason for this is the lack of good estimates of human exposure. In this study exposure was estimated by measurement of isocyanate metabolites in biological samples. METHODS: In a factory using isocyanate based polyurethane (PUR) glue, isocyanate concentrations in air were measured by liquid chromatography. Samples from 174 employees were analysed for metabolites of 4, 4'-methylene diphenyl diisocyanate (MDI) in plasma (P-MDX) and urine (U-MDX). After hydrolysis, 4, 4'-methylenedianiline was measured by gas chromatography-mass spectrometry (GC-MS). The employees were screened for work related respiratory symptoms and tested for specific immunoglobulin E (IgE) and IgG antibodies directed against isocyanate conjugated to human serum albumin. RESULTS: The time weighted isocyanate concentrations in air were low (MDI < 0.2-7; hexamethylene diisocyanate (HDI) < 0.1-0.7; 2, 6-toluene diisocyanate (TDI) < 0.1 microgram/m3). All subjects had detectable P-MDX and U-MDX. There were significant associations between the estimates of exposure to thermal degradation products of an MDI based glue and P-MDX (range < or = 0.10-5.5 micrograms/l); and U-MDX (< or = 0.04-5.0 micrograms/g creatinine); in cases of heavy exposure. P-MDX and U-MDX were associated with each other (r = 0.64; P = 0.0001), work related symptoms (P-MDX: P = 0.03; Mann-Whitney U test), and serum concentrations of MDI specific IgG antibodies (r = 0.26; P = 0.0007). Unexpectedly, high P-MDX and U-MDX concentrations were also encountered in workers cutting textile (P-MDX 2.4-4.5 micrograms/l; U-MDX 0.81-3.8 micrograms/g creatinine); the reason is still unknown. Equally unexpected, there were significant negative associations between P-MDX and liver function tests. CONCLUSIONS: The results clearly show the value of biomarkers for isocyanate exposure; in particular, P-MDX is useful. Further, these results show the risk connected with thermal degradation of PUR.